1996
DOI: 10.1046/j.1365-2125.1996.31610.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concurrent antiepileptic medication on the pharmacokinetics of lamotrigine as add‐on therapy in epileptic children

Abstract: 1 Lamotrigine is a new antiepileptic drug, chemically unrelated to currently used antiepileptic medication. Its pharmacokinetics can be influenced by concomitant antiepileptic medication. 2 This study was performed to assess the pharmacokinetic profile of lamotrigine in three groups of children treated with different types of comedication: drugs known to induce, to inhibit or to have no clinically significant influence on drug metabolism, respectively. 3 Thirty‐one children aged 6 months to 5 years were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…The model validation dataset contained a total of 508 concentrations collected from 148 patients (Table 1) enrolled in four studies, two single‐dose pharmacokinetic studies [18, 19] and two efficacy/safety trials [13, 14] of placebo‐controlled parallel design with LTG or placebo added to the existing AED therapy which was maintained unchanged during the trials (Table 2). The patient characteristics are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model validation dataset contained a total of 508 concentrations collected from 148 patients (Table 1) enrolled in four studies, two single‐dose pharmacokinetic studies [18, 19] and two efficacy/safety trials [13, 14] of placebo‐controlled parallel design with LTG or placebo added to the existing AED therapy which was maintained unchanged during the trials (Table 2). The patient characteristics are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Although most cases of epilepsy are diagnosed during childhood and adolescence, information on the pharmacokinetics of LTG in children is limited [17–19]. Conventional pharmacokinetic studies require extensive blood sampling, and are therefore difficult to conduct in children.…”
Section: Introductionmentioning
confidence: 99%
“…[66] After a single oral dose of 2 mg/kg, a mean maximum plasma concentration (C max ) of 1.48 mg/L (range 0.7 to 2.09 mg/L) was attained after a mean of 4.1 hours in 12 children aged between 6 months and 12 years receiving lamotrigine in the absence of other agents. [57] The time to reach maximum plasma concentrations (t max ) shows wider interindividual variability in children (typically 1 to 6 hours) [57,59] compared with adults (1 to 3 hours). [55] Lamotrigine pharmacokinetics are linear: C max and area under the plasma concentration-time curve (AUC) values are directly proportional to lamotrigine dose in the 30 to 450mg range in both children [61] and adults with epilepsy.…”
Section: Absorption and Distributionmentioning
confidence: 99%
“…Blankenhorn et al (22) found 18 k g LTG/ml serum in one female who swallowed 3,000 mg LTG with suicidal intentions -2 h after ingestion. Comedication with CBZ or PHT has an enzyme-inducing effect (16,23,24) and should reduce the maximal serum concentrations. On the other hand, patients l and 4 received 600 mg ranitidinelday as additional medication.…”
Section: F P Meyer Et Almentioning
confidence: 99%